Executive Compensation and Competition in the Banking and Financial Sectors - Maria Guadalupe; Vicente Cu\~nat (Institute for the Study of Labor (IZA), 2004)
This paper studies the effect of product market competition on the compensation packages that firms offer to their executives and in particular its impact on the sensitivity of pay to performance. To measure the effect of competition we use two different identification strategies on a panel of US executives. We exploit two deregulation episodes in the banking and financial sectors as quasi-natural experiments. We provide difference in differences estimates of the effect of competition on estimated performance-pay sensitivities and on the sensitivity of stock option grants. Our results indicate that a higher level of product market competition increases the performance pay sensitivity of executive compensation schemes.
Keywords: J31; M52; L1; 330; executive compensation; product market competition; performance related pay; Leistungsorientierte Vergütung; Führungskräfte; Bank; Finanzsektor; Wettbewerb; Schätzung; Vereinigte Staaten